Influenza Viral Vectors Expressing Two Kinds of HA Proteins as Bivalent Vaccine Against Highly Pathogenic Avian Influenza Viruses of Clade 2.3.4.4 H5 and H7N9 - Li, Jinping; Hou, Guangyu; Wang, Yan; Wang, Suchun; Peng, Cheng; Yu, Xiaohui; Jiang, Wenming (Frontiers in Microbiology, 2018)
The H5 and H7N9 subtypes of highly pathogenic avian influenza viruses (HPAIVs) in China pose a serious challenge to public health and the poultry industry. In this study, a replication competent recombinant influenza A virus of the Н5N1 subtype expressing the H7 HA1 protein from a tri-cistronic NS segment was constructed. A heterologous dimerization domain was used to combine with A the truncated NS1 protein of 73 amino acids combined with a heterologous dimerization domain was used to increase protein stability. H7 HA1, and nuclear export protein coding information region, and the truncated NS1 were fused in in-frame into a single open reading frame via 2A self-cleaving peptideswith the truncated NS1 open reading frame and separated from each other by 2A self-processing sites. The resulting PR8-H5-NS1(73)H7 stably expressed the H5 HA and H7 HA1 proteins, and exhibited similar growth kinetics as the parental PR8-H5 virus in vitro. PR8-H5-NS1(73)H7 induced specific hemagglutination inhibition (HI) antibody against H5, which was comparable to that of the combination vaccine of PR8-H5 and PR8-H7. The HI antibody titers against H7 virus were significantly lower than that by the combination vaccine. PR8-H5-NS1(73)H7 completely protected chickens from challenge with both H5 and H7 HPAIVs. These results suggest that PR8-H5-NS1(73)H7 is highly immunogenic and efficacious against both H5 and H7N9 HPAIVs in chickens.